C3S–QVCO: A low phase noise low power super–harmonic coupling QVCO with cross–connected common–source nodes. (January 2021) - Mazloum, Jalil; Sheikhaei, Samad
Abstract: In this paper, a novel passive super–harmonic coupling QVCO is presented. The coupling is achieved by Cross–Connecting the top and bottom Common–Source nodes in the complementary (current reuse) LC Cross–Coupled oscillator topology, and therefore, the circuit is named as C3S–QVCO. Unlike the transformer coupling QVCO (TC–QVCO), as the typical super–harmonic coupling technique, the die area is not increased. Also, in the proposed QVCO, neither additional power consumption nor additional noise generator component is required, for quadrature operation. Therefore, the proposed QVCO has a good power consumption performance. The proposed method is evaluated theoretically and analytically, and it is proved that the proposed method is capable of generating multi–phase outputs. The proposed QVCO is designed in a 0.18 ​μm RF–CMOS technology with a power supply of 1.8 ​V, the current consumption of 6.25 ​mA, and the tuning range of 3.75–3.95 ​GHz (5.3%). Post layout simulation result shows −129 ​dBc/Hz, and 190 ​dB phase noise and FOM for the proposed QVCO at 1 ​MHz offset from the 3.75 ​GHz frequency. The proposed QVCO presents 6 ​dB phase noise improvement compared to parallel (P)–QVCO and also demonstrates similar phase noise performance to that of the TC–QVCO, with the same power consumption. Maximum phase/amplitude errors of the proposed QVCO for a 1% mismatch in the oscillator's tank capacitors are 0.72°/2 ​mV, in the whole tuning range. Those are 0.77°/7.3 ​mV for the P–QVCO and 1.3°/2.3 ​mV for the TC–QVCO. Graphical abstract: Image 1